Quality of Service in Multiservice IP Networks Third International Workshop, QoS-IP 2005, Catania, Italy, February 2-4, 2004, Catania, Italy, February 2-4, 2004. Proceedings - Ajmone Marsan, Marco; Bianchi, Giuseppe; Listanti, Marco; Meo, Michela (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
This book constitutes the refereed proceedings of the Third International Workshop on Quality of Service in Multiservice IP Networks, QoS-IP 2005, held in Catania, Italy in February 2005. The 50 revised full papers presented were carefully reviewed and selected from around 100 submissions. The papers are organized in topical sections on analytical models, traffic characterization, MPLS failure and restoration, network planning and dimensioning, DiffServ and InfServ, routing, software routers, network architectures for QoS provisioning, multiservice in wireless networks, TCP in special environments, and scheduling.
Analytical Models -- An Analytical Model of a New Packet Marking Algorithm for TCP Flows -- Of Mice and Models -- A Dual Approach to Network Calculus Applying the Legendre Transform -- Service Curve Estimation by Measurement: An Input Output Analysis of a Softswitch Model -- Utility Proportional Fair Bandwidth Allocation: An Optimization Oriented Approach -- Traffic Characterization -- Packet Size Distribution: An Aside? -- Synthesis and MAVAR Characterization of Self-similar Traffic Traces from Chaotic Generators -- Coupled Kermack-McKendrick Models for Randomly Scanning and Bandwidth-Saturating Internet Worms -- On-Line Segmentation of Non-stationary Fractal Network Traffic with Wavelet Transforms and Log-Likelihood-Based Statistics -- MPLS Failure and Restoration -- Implementation of Virtual Path Hopping (VPH) as a Solution for Control Plane Failures in Connection Oriented Networks and an Analysis of Traffic Distribution of VPH -- Experimental Comparison of Fault Notification and LSP Recovery Mechanisms in MPLS Operational Testbeds -- NPP: A Facility Based Computation Framework for Restoration Routing Using Aggregate Link Usage Information -- An Efficient Backup Path Selection Algorithm in MPLS Networks -- Network Planning and Dimensioning -- Planning Multiservice VPN Networks: An Analytical/Simulative Mechanism to Dimension the Bandwidth Assignments -- Topological Design of Survivable IP Networks Using Metaheuristic Approaches -- Replicated Server Placement with QoS Constraints -- Dimensioning Approaches for an Access Link Assuring Integrated QoS -- Aggregation Network Design for Offering Multimedia Services to Fast Moving Users -- DiffServ and IntServ -- Management of Non-conformant TCP Traffic in IP DiffServ Networks -- Performance of Active Queue Management Algorithms to Be Used in Intserv Under TCP and UDP Traffic -- An Analytical Framework to Design a DiffServ Network Supporting EF-, AF- and BE-PHBs -- A Performance Model for Multimedia Services Provisioning on Network Interfaces -- An Integrated Multi-service Software Simulation Platform: SIMPSONS Architecture -- Routing I -- Optimal Load Balancing in Insensitive Data Networks -- Hybrid IGP+MPLS Routing in Next Generation IP Networks: An Online Traffic Engineering Model -- Leveraging Network Performances with IPv6 Multihoming and Multiple Provider-Dependent Aggregatable Prefixes -- Software Routers -- Open-Source PC-Based Software Routers: A Viable Approach to High-Performance Packet Switching -- Performance of a Software Router Using AltQ/CBQ – A Measurement-Based Analysis -- Comparative Analysis of SMP Click Scheduling Techniques -- Implementation of Implicit QoS Control in a Modular Software Router Context -- Network Architectures for QoS Provisioning -- Should IP Networks Go Multiservices? -- The Impact of Revenues on Delivering Differentiated IP Multimedia Services in Wired/Wireless Networks -- Architecture and Protocols for the Seamless and Integrated Next Generation IP Networks -- Bandwidth Management in IntServ to DiffServ Mapping -- Routing II -- Optimizing Routing Decisions Under Inaccurate Network State Information -- On the Performance of Dynamic Online QoS Routing Schemes -- A Dynamic QoS-Aware Transmission for Emergency Traffic in IP Networks -- Unicast and Multicast QoS Routing with Multiple Constraints -- Multiservice Wireless Networks -- Q-MEHROM: Mobility Support and Resource Reservations for Mobile Hosts in IP Access Networks -- 802.11 MAC Protocol with Selective Error Detection for Speech Transmission -- Performance Evaluation of a Feedback Based Dynamic Scheduler for 802.11e MAC -- QoS Routing in Multi-hop Wireless Networks: A New Model and Algorithm -- Transient QoS Measure for Call Admission Control in WCDMA System with MIMO -- TCP in Special Environments -- Adaptive Bandwidth Partitioning Among TCP Elephant Connections over Multiple Rain-Faded Satellite Channels -- On the Performance of TCP over Optical Burst Switched Networks with Different QoS Classes -- Loss Differentiation Schemes for TCP over Wireless Networks -- Scheduling -- Revenue-Based Adaptive Deficit Round Robin -- A Shift Varying Filtering Theory for Dynamic Service Guarantees -- Robust Delay Estimation of an Adaptive Scheduling Algorithm -- Input Register Architectures of High Speed Router for Supporting the PHB of Differentiated Services.
SpringerLink eBooks.
Keywords: Computer science; Computer communication systems; Software engineering; Information storage and retrieval; Management information systems; Electrical engineering; Computer Science; Computer Communication Networks; Software Engineering; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Management of Computing and Information Systems; Communications Engineering, Networks